2020
DOI: 10.2106/jbjs.oa.20.00133
|View full text |Cite
|
Sign up to set email alerts
|

Nonoperative Treatment of Anterior Glenoid Rim Fractures After First-Time Traumatic Anterior Shoulder Dislocation

Abstract: Background: Primary traumatic anterior shoulder dislocations can be associated with displaced anterior glenoid rim fractures. Nonoperative treatment of such fractures has been shown to have excellent results in a small cohort of patients; as such, we have been treating these fractures nonoperatively, regardless of fragment size and degree of displacement, provided that post-reduction computed tomography scans revealed an anteroposteriorly centered humeral head. The aim of this study was to analyze t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 26 publications
1
20
0
3
Order By: Relevance
“…A further study confirmed those results in ten patients, and no recurrence or signs of clinical instability were reported [18]. Within these studies, no further complications or concomitant lesions were found [18,21,38]. Salomonsson et al reviewed 12 cases of GRF and found that bony bankart was a positive predictive factor for stability [30].…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…A further study confirmed those results in ten patients, and no recurrence or signs of clinical instability were reported [18]. Within these studies, no further complications or concomitant lesions were found [18,21,38]. Salomonsson et al reviewed 12 cases of GRF and found that bony bankart was a positive predictive factor for stability [30].…”
Section: Discussionmentioning
confidence: 54%
“…Thus, in our eyes, the age of the patient group has to be considered for interpretation of the data because of the well-known fact that younger individuals have a higher risk for recurrence [22,29,36]. This finding is confirmed by the fact that the patient series of the above-mentioned studies of non-operative treated GRF had a mean age of 53 years [21], 57 years [18] and 48 years with only one case of instability [38].…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations